(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The most important thing that infrastructure projects represent are water and sanitation projects. The current reality faces the lack of audit procedures within the main audit program for infrastructure projects approved by the relevant Federal Board of Supreme Audit. Relevant to achieving the Sustainable Development Goal (Sixth), which relates to (ensuring the availability and sustainability of water and sanitation management for all), which requires strengthening these programs with additional audit procedures that include indicators of this goal. The research seeks to focus on linking infrastructure projects with the goals of sustainable development and applying the objectives of the sustainable development goal (sixth) to demonstrate the role and contribution of the aforementioned infrastructure projects in achieving this goal, and preparing additional audit procedures (procedures for auditing the strategic plan for sustainable development goals, and procedures for auditing economic feasibility studies). The technical audit for infrastructure projects related to Sustainable Development Goal (SDG VI) enhances the main audit program for those projects. The researcher reached a set of conclusions, the most important of which is that the audit programs prepared by the Federal Board of Supreme Audit did not include audit procedures for indicators of the sustainable development goal related to infrastructure projects, and there is no interest on the part of the governorate in sustainable development and its goals, and there is no follow-up by the Ministry of Planning on the governorate regarding that. The researcher did not find any difficulty in achieving the sustainable development goal (sixth) if the governorate implemented these projects. The most prominent recommendations were the need to establish a specific mechanism by the Federal Board of Supreme Audit to follow up on achieving the goal of sustainable development related to infrastructure projects through audit procedures that take into account the indicators of that goal, and to exert more care and attention to sustainable development and its goals by the governorate, with the Ministry of Planning following up on that to coincide with the follow-up. The Bureau, with the need to make more efforts to achieve the sustainable development goal (sixth).